Association of Burnout with Workforce-Reducing Factors among EMS Professionals. (4th March 2018) - Crowe, Remle P.; Bower, Julie K.; Cash, Rebecca E.; Panchal, Ashish R.; Rodriguez, Severo A.; Olivo-Marston, Susan E.
Abstract: Objectives : Emergency medical services (EMS) professionals often work long hours at multiple jobs and endure frequent exposure to traumatic events. The stressors inherent to the prehospital setting may increase the likelihood of experiencing burnout and lead providers to exit the profession, representing a serious workforce and public health concern. Our objectives were to estimate the prevalence of burnout, identify characteristics associated with experiencing burnout, and quantify its relationship with factors that negatively impact EMS workforce stability, namely sickness absence and turnover intentions. Methods : A random sample of 10, 620 emergency medical technicians (EMTs) and 10, 540 paramedics was selected from the National EMS Certification database to receive an electronic questionnaire between October, 2015 and November, 2015. Using the validated Copenhagen Burnout Inventory (CBI), we assessed burnout across three dimensions: personal, work-related, and patient-related. We used multivariable logistic regression modeling to identify burnout predictors and quantify the association between burnout and our workforce-related outcomes: reporting ten or more days of work absence due to personal illness in the past 12 months, and intending to leave an EMS job or the profession within the next 12 months. Results : Burnout was more prevalent among paramedics than EMTs (personal: 38.3% vs. 24.9%, work-related: 30.1% vs. 19.1%, and patient-related: 14.4% vs. 5.5%). Variables associated with increased burnout in all dimensions included certification at the paramedic level, having between five and 15 years of EMS experience, and increased weekly call volume. After adjustment, burnout was associated with over a two-fold increase in odds of reporting ten or more days of sickness absence in the past year. Burnout was associated with greater odds of intending to leave an EMS job (personal OR:2.45, 95% CI:1.95–3.06, work-related OR:3.37, 95% CI:2.67–4.26, patient-related OR: 2.38, 95% CI:1.74–3.26) or the EMS profession (personal OR:2.70, 95% CI:1.94–3.74, work-related OR:3.43, 95% CI:2.47–4.75, patient-related OR:3.69, 95% CI:2.42–5.63). Conclusions : The high estimated prevalence of burnout among EMS professionals represents a significant concern for the physical and mental well-being of this critical healthcare workforce. Further, the strong association between burnout and variables that negatively impact the number of available EMS professionals signals an important workforce concern that warrants further prospective investigation.